Evolution and relationships of the conifer seed cone telemachus: Evidence from the triassic of antarctica - Escapa, Ignacio Hernán (2010)
The seed cone Telemachus is known from several Triassic localities in Gondwana. New specimens from two localities in Antarctica provide additional information about the type species, Telemachus elongatus, based on details of morphology and anatomy revealed by using a modified transfer technique on the compressed plants. Seed cones of T. elongatus are up to 6.0 cm long and characterized by conspicuous, elongate bracts. A second Antarctic species, described here as Telemachus antarcticus, is segregated, based on a shorter bract and differences in cone size. Newly recognized features of the genus include the shape, size, and disposition of the ovules; vascularization of the ovuliferous complex; and scale and bract histology. As a result of this new information, it is now possible to compare Telemachus with the permineralized Middle Triassic conifer seed cone Parasciadopitys from the Central Transantarctic Mountains. The similarities between the two genera make it possible to relate organs in different preservational modes and to develop a more complete concept for this widely distributed Gondwana conifer. Placing the Telemachus plant within a phylogenetic context makes it possible to evaluate the relationship with other so-called transitional conifers, an informal group that has been interpreted as intermediate between Paleozoic and modern conifers.